THE INFLUENCE OF COMPETENCE AND COMPENSATION ON THE PERFORMANCE OF ACADEMIC STAFF EMPLOYEES WITHIN THE FACULTY OF TARBIYAH AND KEGURUAN UIN ALAUDDIN MAKASSAR - Masmur. M (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2024)
This study aims to determine the partial and simultaneous effects of competence and compensation on the performance of academic staff employees within the Faculty of Tarbiyah and Keguruan UIN Alauddin Makassar. The research method used is quantitative research method with data collection techniques through questionnaires. Research data were taken from 52 academic staff employees within the Faculty of Tarbiyah and Keguruan. The results showed that competence had a significant effect on employee performance with a t-count> t-table value of 2.187> 2.0098, and the significance value was 0.034 <0.05. Compensation also has a significant effect with the value of t-count> t-table is 2.217> 1.0098 and the significance value is 0.031 <0.05. Simultaneously competence and compensation have a significant effect with the value of F-count> F-table is 17.814> 3.18 and the significance value is 0.00 <0.05. The contribution of influence or determination of competency and compensation variables to the performance of academic staff employees in the Faculty of Tarbiyah and Keguruan is 42.1%.